2016
DOI: 10.1007/s10930-016-9672-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Miscellaneous Peptides from the Skin Secretion of the European Edible Frog, Pelophylax kl. Esculentus

Abstract: The chemical compounds synthesised and secreted from the dermal glands of amphibian have diverse bioactivities that play key roles in the hosts' innate immune system and in causing diverse pharmacological effects in predators that may ingest the defensive skin secretions. As new biotechnological methods have developed, increasing numbers of novel peptides with novel activities have been discovered from this source of natural compounds. In this study, a number of defensive skin secretion peptide sequences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To date, more than thirty different AMPs have been discovered from the edible frog [2][3][4][5][6][7][8][9], most of which are brevinins [4,[6][7][8], esculentins [4] and temporins [5,6,9,10]. Besides, there are also protease inhibitors [11] and bradykinins [12] in the skin secretions of P. kl.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than thirty different AMPs have been discovered from the edible frog [2][3][4][5][6][7][8][9], most of which are brevinins [4,[6][7][8], esculentins [4] and temporins [5,6,9,10]. Besides, there are also protease inhibitors [11] and bradykinins [12] in the skin secretions of P. kl.…”
Section: Introductionmentioning
confidence: 99%
“…esculentus have a more significant influence on the immune system to defend against invaders, and they have more potent anti-fungal activity and stability than those peptides from the parent frogs such that they are deserving of further research [ 58 ]. The AMPs extracted from the skin secretion of this frog are mainly brevinins, esculentins, and temporins, which possess potent effects against microorganisms [ 59 ]. For instance, temporin-PE displays a more potent antimicrobial activity against different kinds of pathogens than other peptides extracted from Pelophylax kl.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although a bombesin-related peptide has been found in the skin secretion of Pelophylax kl. esculentus [ 26 ], our study identified a novel bombesin propeptide from Pelophylax kl. esculentus , and confirmed the mature peptide in the skin secretion.…”
Section: Discussionmentioning
confidence: 99%